UJI PRAKTIKALITAS PERANGKAT EKSPERIMEN FLUIDA STATIS SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Suci Aulia Risti; Zulhelmi Zulhelmi; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to determine the level of practicality of static fluid experiment kits and worksheets for experimental guides to the concept of static fluids, so as to produce a learning media that is feasible and practical to be used as a media for teaching Physics Science in Junior High School. The object of this study is an experimental device consisting of a static fluid experiment kit and an experiment guide book. The research method used is research and development. Data collection techniques used a practicality assessment sheet given to respondents consisting of 20 students and 3 science teachers at Muhammadiyah 1 Pekanbaru junior high school.Data were analyzed descriptively to determine the value of the practicality of the experimental device. Descriptive analysis shows that the practicality of the static fluid experiment kit is in the very high category with an average score of 3.32 and 3.36. As well, the assessment of the practicality of the Student Worksheets was very high by teachers and students with an average score of 3.42 and 3.58. Therefore the experimental device along with the student worksheet experiment guide for the concept of static fluid is declared practical to be used as a media for learning physics at junior high school.KeyWords:Experimental Tool, Static Fluid, Student Worksheets, Practicality, Learning Media